IMPLEMENTASI FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP PELAKSANAAN PERATURAN DAERAH OLEH KEPALA DAERAH DI KABUPATEN CILACAP (STUDI PADA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN CILACAP PERIODE 2004 â 2009) - , MUHAMMAD SYAIFUL ANWAR; , Fajrul Falaakh, S.H., MA., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is done based on the fact that the supervision done by Local Legislative Council of Cilacap is very weak. There is gap between the goal want to be achieve by local regulation of those regulation. Problem raised in this research are : 1). How is the supervision done by DPRD on the implementation of local regulation by the regent based on law no. 32 of 2004 in Cilacap, 2). Obstacles faced by local legislative council in controlling the implementation of local regulation in Cilacap. This research aims to analyze the effectiveness of supervision done by local legislation council of Cilacap to the implementation of region regulation and obstacles faced by local legislative council in controlling the implementation of those regulation. This research uses empirical normative. Method in normative legal research document, positive law and literatures are studied as secondary data. Proximity and relevancy used as a law material to be included in particular criteria such as primary, secondary and tertiary. In addition in field legal research data is taken from direct field research of the object. This research was done with depth interview and data were analyzed using qualitative descriptive analysis. This research shows that supervision done by local legislative council was not optimal. There are obstacles found are: the supervision done by local legislative council is very weakness to local government, is not including lack of rules concerning the supervision of Local Legislative Council against the system parliament yet, and his little oversight authority of Local Legislative Council. In addition this research are, need preparation for supervision, continuous monitoring system, and harmonization of rules on supervision function.